Soekarno in PDI perjuangan billboards as an intention to perpetuate power: a study of critical discourse analysis - Ratri, Risalah Damar; Rizky Abrian (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
The language and signs discussed in the public space by various political parties are known to be related to politics and power, namely that the two are interrelated. Something that political parties construct has a specific purpose. This study aims to dissect the hidden discourses of Ir. Soekano in PDI Perjuangan billboards through the application of Michel Foucault's theory of power- knowledge Utilizing a descriptive qualitative design with primary data sources of PDI Perjuangan billboards in public places and data in the form of the name and portrait of Ir. Soekarno in billboards and secondary data in the form of data on the internet regarding the PDI Perjuangan. The data collection technique was carried out by purposive sampling. The data analysis applies the Miles & Huberman triangulation model, including data reduction, presentation, and verification. The results obtained include; (1) interpretation of Megawati's knowledge of the privileges and prestige she has, displays the image of a symbolic leader, and is represented through Ir Soekarno's object in the PDI Perjuangan billboard; (2) Ir. Soekarno, in the PDI Perjuangan billboard, attempted to perpetuate the PDI Perjuangan power from the people's voice.